PROFILE OF AN EARLY-CHILDHOOD TEACHING GRADUATE - HONZIKOVA, Jarmila; PODPERA, Milan (Trends in education, 2013)
The article conducts a study of the profile of an early-childood teaching graduate, discussing his competencies as well as comparing the capacity related fulfillment of his individual professional competencies.
Keywords: study of an early-childood teaching graduate; profile of graduate.